Digital competence and leadership in educational supervisors: challenges and perspectives from the role of district teaching technicians: Dominican Republic - de la Cruz Morla, Leonel (Avances en Supervisión Educativa, 2022)
Digital competence and leadership have become two fundamental elements for the performance of the functions of educational supervisors. Indeed, this research aims to reflect on how digital competence and the leadership of educational supervisors are addressed in the scientific literature with a view to performing their functions in an efficient, innovative and collaborative manner in the information age. For this, a bibliographic review has been developed, using as a source various investigations and documents where the level of digital competence that the educational supervisor must have and the leadership skills are revealed, making a reflection of its incidence in the plane of the pedagogical and administrative processes. The results obtained show that the combination of digital competence and leadership has a set of unavoidable skills for educational supervisors; In addition, the need to promote these areas in these educational agents is evident, given the importance of ICT and TAC to guide and guide pedagogical practices, making efficient, adequate and collaborative use.